Treatment of an aneurysmal bone cyst in a young dog: A case report. Issue 2 (9th February 2022) - Olimpo, Matteo; Del Magno, Sara; Morello, Emanuela; Lenarduzzi, Giulio; Buracco, Paolo; Piras, Lisa Adele
Abstract: Background: An aneurysmal bone cyst (ABC) is a rare benign lytic lesion affecting the medullary canal of long bones. It has been widely reported in human medicine, but rarely described in domestic animals. Objective: To report the surgical treatment and long term follow‐up of a dog affected by ABC. Methods: An 8‐month‐old, intact female Weimaraner was presented with lameness affecting the left front limb and progressive swelling of the mid‐distal radius. Survey radiographs revealed a mid‐distal diaphyseal radial lesion. Fine needle aspirates, biopsy, CT scan and histopathology results supported the diagnosis of ABC. Treatment consisted of partial corticotomy of the affected radius, filling of the cystic cavity with demineralised bone matrix and autologous bone graft and stabilisation using lag screws and a neutralisation plate. Results: The long‐term follow‐up, at 36 post‐operative months, showed no recurrence of the cyst and bone modelling. Comparing preoperative radiographs with those at 36 months, bone modelling reduced the radial area by 23.3% in the craniocaudal radiographic view and 30% in the mediolateral projection. Conclusions: This treatment was sucessful in the case here described, with a 3 years follow‐up. Abstract : An eight‐month‐old, intact female Weimaraner was presented with lameness affecting the left front limb and progressive swelling of the mid‐distal radius. Survey radiographs revealed a mid‐distal diaphyseal radial lesion. Fine needle aspirates, biopsy, CT scan and histopathology results supported the diagnosis of ABC. Treatment consisted of partial corticotomy of the affected radius, filling of the cystic cavity with demineralised bone matrix and autologous bone graft, and stabilisation using lag screws and a neutralisation plate.